Evaluation of nutraceutical properties of selected small millets - B Raghavendra Rao; Manojkumar H Nagasampige; M Ravikiran (Wolters Kluwer Medknow Publications, 2011)
Objective: The aim of this study was to evaluate the nutraceutical properties and nutritional value of grains of four selected small millets viz. finger millet, foxtail millet, prosomillet and khodomillet. Materials and Methods: The qualitative analysis of phytochemicals viz. phenolics, flavonoids, alkaloids and saponins present in the four small millets was done. The water-soluble proteins, crude fiber content and the reducing power of the grains of these four millets were analyzed. Results and Conclusions: The khodomillet showed maximum phenolic content (10.3%) and foxtail millet showed minimum phenolics (2.5%). As far as reducing capacity was concerned, finger millet was highest (5.7%). The prosomillet showed least reducing property (2.6%). The finger millet (391.3 mg/g each) showed maximum reducing sugar content. The prosomillet showed minimum reducing sugar (195 mg/g). The foxtail millet showed maximum protein content (305.76 mg/g) and prosomillet showed minimum protein content (144.23 mg/g). The khodomillet showed maximum crude fiber content (14.3%).The finger millet showed maximum reducing sugar content (391.3 mg/g) whereas, the khodomillet showed minimum reducing sugar (130.43 mg/g).